Improving the sustainability and quality of kidney health care through life cycle assessments, quality improvement, education and technical innovations: the KitNewCare approach - Duane, Brett; Johnston, Bridget (My University, 2024)
The KitNewCare consortium aims to create and manage a comprehensive EU-wide programme focusing on sustainability in Kidney Care. The burden of chronic kidney disease is significant and increasing. Around 850 million people have the disease worldwide and by 2030 6 million will need kidney replacement therapy, mainly haemodialysis. As the world population gets older, projections for the end of the century worsen. From a sustainability perspective, healthcare systems contribute around 5-11% of total carbon emissions. Kidney care is one of the most resource intensive specialties. In addition to energy, haemodialysis requires transportation of patients and personnel to and from facilities, uses large volumes of water and generates significant plastic waste. Overall, current dialysis is not sustainable in the medium term. Primary prevention, implementing early diagnosis and treatment of CKD and transplantation will decrease the need for dialysis, but this will take time and even such measures will not prevent the need for dialysis in millions of persons. There is a need to improve knowledge around both the environmental and financial cost of kidney care and also the social and health outcomes of each patient pathway. There is a need for workflow optimizations, organisational transformations and technological innovations across Europe, and a need to learn from different clinical sites. KitNewCare will build a European-wide knowledgebase for sustainability in kidney care, develop and introduce a 4-factor life cycle assessment database for comprehensive impact analysis, implement optimized processes and organizational transformations in four European clinical sites. It will pilot innovations from high-tech small- and medium-sized enterprises with focus on Kidney care, and establish a network for continuous monitoring, benchmarking, and implementation of sustainable solutions across healthcare sectors.
PUBLISHED
Keywords: Carbon footprint; Environmental sustainability; Carbon footprint; Kidney care; CARBON CYCLE; GLOBAL CLIMATE-CHANGE; Renal diseases, chronic renal failure, transplantation; Health